Associations between respiratory sinus arrhythmia (RSA) reactivity and effortful control in preschool‐age children. Issue 5 (2nd May 2015) - Sulik, Michael J.; Eisenberg, Nancy; Spinrad, Tracy L.; Silva, Kassondra M.
ABSTRACT We tested whether respiratory sinus arrhythmia (RSA) reactivity in response to each of three self‐regulation tasks (bird and dragon; knock‐tap; and gift wrap) would predict self‐regulation performance in a sample of 101 preschool‐age children (M age = 4.49, SD = .64). While controlling for baseline RSA, decreases in RSA from bird and dragon to knock‐tap (but not from baseline to bird and dragon) predicted a latent variable measuring self‐regulation. Furthermore, increases in RSA from the knock‐tap to gift wrap—the only task involving delay of gratification—were related to concurrent task performance while controlling for the relation between RSA reactivity and the latent self‐regulation variable. Results suggest that the relations between RSA reactivity and self‐regulatory ability are influenced by task‐specific demands and possibly by task order. Furthermore, RSA reactivity appears to relate differently to performance on motivationally salient self‐regulation tasks such as delay of gratification relative to cool executive function tasks. © 2015 Wiley Periodicals, Inc. Dev Psychobiol 57: 596–606, 2015.